2023
DOI: 10.1051/0004-6361/202245219
|View full text |Cite
|
Sign up to set email alerts
|

The multiplicity fraction in 202 open clusters from Gaia

Abstract: In this study, we estimate the fraction of binaries with high mass ratios for 202 open clusters in the extended solar neighbourhood (closer than 1.5 kpc from the Sun). This is one of the largest homogeneous catalogues of multiplicity fractions in open clusters to date, including the unresolved and total (close-binary) multiplicity fractions of main-sequence systems with mass ratio greater than $ 0.6_{ -0.15}^{+0.05} $. The unresolved multiplicity fractions were estimated applying a flexible mixture model to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Our estimated BF for NGC 6819 is 25.72% ± 4.34%, slightly higher than the results (22% ± 3%) obtained by Milliman et al (2014) based on 93 spectroscopic binaries. The subplot in Figure 9 shows the relationship between BF and age, and the trend is consistent with that of Donada et al (2023) (red dashed line).…”
Section: Binary Fractionsupporting
confidence: 59%
“…Our estimated BF for NGC 6819 is 25.72% ± 4.34%, slightly higher than the results (22% ± 3%) obtained by Milliman et al (2014) based on 93 spectroscopic binaries. The subplot in Figure 9 shows the relationship between BF and age, and the trend is consistent with that of Donada et al (2023) (red dashed line).…”
Section: Binary Fractionsupporting
confidence: 59%
“…In general, our results for the binary fraction (after completeness correction) are in agreement with their results, except for three clusters: Alessi 9, NGC 1901, and NGC 3228. For these clusters, we find higher binary fractions than Donada et al (2023). This difference might be attributed to the different lower limit for the mass ratio (q > 0.6 in Donada et al 2023) adopted when calculating the binary fraction.…”
Section: Crossmatch With Previous Workmentioning
confidence: 52%
“…30 clusters in our sample are also described in the study of Donada et al (2023). The latter study also carried out distancedependent completeness corrections for the binary fraction.…”
Section: Crossmatch With Previous Workmentioning
confidence: 99%
“…However, we do not find any trend of binary fraction with the number of relaxation times. Some previous studies of photometric binaries in OCs have also observed such a trend between binary fraction and cluster age (Donada et al 2023), while others have not (Pang et al 2023; see also Section 5.4). However, many of these previous studies employ less reliable techniques to identify photometric binaries (i.e., "chi by eye").…”
Section: Impacts Of Stellar Dynamics and Relaxationmentioning
confidence: 84%